A note on Golomb topologies. Issue 1 (2nd January 2019) - Clark, Pete L.; Lebowitz-Lockard, Noah; Pollack, Paul
Abstract: In 1959 Golomb defined a connected topology on ℤ. An analogous Golomb topology on an arbitrary integral domain was defined first by Knopfmacher-Porubský [KP97] and then again in a recent work of Clark [Cl17]. Here we study properties of Golomb topologies.